Incentive Audits : A New Approach to Financial Regulation - Čihák, Martin (World Bank, Washington, DC, 2013)
A large body of evidence points to misaligned incentives as having a key role in the run-up to the global financial crisis. These include bank managers' incentives to boost short-term profits and create banks that are "too big to fail," regulators' incentives to forebear and withhold information from other regulators in stressful times, and credit rating agencies' incentives to keep issuing high ratings for subprime assets. As part of the response to the crisis, policymakers and regulators also attempted to address some incentive issues, but various outside observers have criticized the response for being insufficient. This paper proposes a pragmatic approach to re-orienting financial regulation to have at its core the objective of addressing incentives on an ongoing basis. Specifically, the paper proposes "incentive audits" as a tool that could help in identifying incentive misalignments in the financial sector. The paper illustrates how such audits could be implemented in practice, and what the implications would be for the design of policies and frameworks to mitigate systemic risks.